Experimental Study of Fiber Length and Orientation in Injection Molded Natural Fiber/Starch Acetate Composites - Heidi Peltola; Bo Madsen; Roberts Joffe; Kalle Nättinen (Advances in Materials Science and Engineering)
Composite compounds based on triethyl citrate plasticized starch acetate and hemp and flax fibers were prepared by melt processing. Plasticizer contents from 20 to 35 wt% and fiber contents of 10 and 40 wt% were used. The compounded composites were injection molded to tensile test specimens. The effect of processing, melt viscosity and fiber type on the fiber length was investigated. The lengths of fully processed fibers were determined by dissolving the matrix and measuring the length of the remaining fibers by microscope analysis. A clear reductive effect of the processing on the fiber length was noticed. A reduction of fiber length along the increasing fiber content and the decreasing plasticizer content was also detected. This reduction originated from the increasing shear forces during compounding, which again depended on the increased viscosity of the material. Hemp fibers were shown to remain longer and fibrillate more than flax fibers, leading to higher aspect ratio. Thus, the reinforcement efficiency of hemp fibers by the processing was improved, in contrast with flax fibers. In addition, the analysis of fiber dispersion and orientation showed a good dispersion of fibers in the matrix, and a predominant orientation of the fibers in the melt flow direction.